Saccharification of ozonated sugarcane bagasse using enzymes from Myceliophthora thermophila JCP 1-4 for sugars release and ethanol production - de Cassia Pereira, Josiani [UNESP] (2016)
The saccharification of ozonated sugarcane bagasse (SCB) by enzymes from Myceliophthora thermophila JCP 1-4 was studied. Fungal enzymes provided slightly higher sugar release than commercial enzymes, working at 50 °C. Sugar release increased with temperature increase. Kinetic studies showed remarkable glucose release (4.99 g/L, 3%. w/w dry matter) at 60 °C, 8 h of hydrolysis, using an enzyme load of 10 FPU (filter paper unit). FPase and β-glucosidase activities increased during saccharification (284% and 270%, respectively). No further significant improvement on glucose release was observed increasing the enzyme load above 7.5 FPU per g of cellulose. Higher dry matter contents increased sugars release, but not yields. The fermentation of hydrolysates by Saccharomyces cerevisiae provided glucose-to-ethanol conversions around to 63%.